ChemInform Abstract: Silver(I)‐Mediated Three‐Component Annulation Reaction of [60]Fullerene, Sulfonylhydrazones, and Nitriles: Leading to Diverse Disubstituted [60]Fullerene‐Fused Dihydropyrroles. Issue 9 (February 2016) - Chao, Di; Liu, Tong‐Xin; Ma, Nana; Zhang, Pengling; Fu, Zheng; Ma, Jinliang; Liu, Qingfeng; Zhang, Fengjin; Zhang, Zhiguo; Zhang, Guisheng
Abstract: A novel Ag(I)‐induced three‐component annulation reaction of C60 ‐fullerene with sulfonylhydrazones and nitriles is developed for the efficient synthesis of diverse disubstituted C60 ‐fullerene‐fused dihydropyrroles.